Can Big History and Cosmic History Help America Tell its Own Story? Applying Ted Peters' Work to our Future. Issue 3 (3rd July 2021) - Nelson, Derek
ABSTRACT: Because ideology is basically inevitable, we ought to make clear the materialist ideology at work in the story of the cosmos told by Big History. Ted Peters' book, God in Cosmic History, exposes the Big History ideology when introducing a theological rendering of the same story of our universe. Ideology need only be made transparent, not eliminated. Perhaps this observation could aid current re-writers of American history to tell the story honestly, the story that includes chapters on both slavery and liberation. Might this lead America to cross a new threshold of possible axial import?